Vaccinia virus proteins A52 and B14 Share a Bcl-2-like fold but have evolved to inhibit NF-kappaB rather than apoptosis. - Graham, S; Bahar, M; Cooray, S; Chen, R; Whalen, D; Abrescia, N; Alderton, D; Owens, R; Stuart, D; Smith, G; Grimes, J (Public Library of Science, 2008)
Vaccinia virus (VACV), the prototype poxvirus, encodes numerous proteins that modulate the host response to infection. Two such proteins, B14 and A52, act inside infected cells to inhibit activation of NF-kappaB, thereby blocking the production of pro-inflammatory cytokines. We have solved the crystal structures of A52 and B14 at 1.9 A and 2.7 A resolution, respectively. Strikingly, both these proteins adopt a Bcl-2-like fold despite sharing no significant sequence similarity with other viral or cellular Bcl-2-like proteins. Unlike cellular and viral Bcl-2-like proteins described previously, A52 and B14 lack a surface groove for binding BH3 peptides from pro-apoptotic Bcl-2-like proteins and they do not modulate apoptosis. Structure-based phylogenetic analysis of 32 cellular and viral Bcl-2-like protein structures reveals that A52 and B14 are more closely related to each other and to VACV N1 and myxoma virus M11 than they are to other viral or cellular Bcl-2-like proteins. This suggests that a progenitor poxvirus acquired a gene encoding a Bcl-2-like protein and, over the course of evolution, gene duplication events have allowed the virus to exploit this Bcl-2 scaffold for interfering with distinct host signalling pathways.